Potent cytochrome P450 2C19 genotype-related interaction between voriconazole and the cytochrome P450 3A4 inhibitor ritonavir - Mikus, Gerd; Schöwel, Verena Jennifer Johanna; Ten Hoevel, Magdalena Maria; Rengelshausen, Jens; Ding, Reinhard; Riedel, Klaus-Dieter; Burhenne, Jürgen; Weiß, Johanna; Thomsen, Torben; Haefeli, Walter E. (Clinical pharmacology & therapeutics, 2006)
Objectives Cytochrome P450 (CYP) 2C19 and CYP3A4 are the major enzymes responsible for voriconazole elimination. Because the activity of CYP2C19 is under genetic control, the extent of inhibition with a CYP3A4 inhibitor was expected to be modulated by the CYP2C19 metabolizer status. This study thus assessed the effect of the potent CYP3A4 inhibitor ritonavir after short-term administration on voriconazole pharmacokinetics in extensive metabolizers (EMs) and poor metabolizers (PMs) of CYP2C19. Methods In a randomized, placebo-controlled crossover study, 20 healthy participants who were stratified according to CYP2C19 genotype received oral ritonavir (300 mg twice daily) or placebo for 2 days. Together with the first ritonavir or placebo dose, a single oral dose of 400 mg voriconazole was administered. Voriconazole was determined in plasma and urine by liquid chromatography-mass spectrometry, and pharmacokinetic parameters were estimated by noncompartmental analysis. Results When given alone, the apparent oral clearance of voriconazole after single oral dosing was 26% ± 16% (P > .05) lower in CYP2C19*1/*2 individuals and 66% ± 14% (P < .01) lower in CYP2C19 PMs. The addition of ritonavir caused a major reduction in voriconazole apparent oral clearance (354 ± 173 mL/min versus 202 ± 139 mL/min, P = .0001). This reduction occurred in all CYP2C19 genotypes (463 ± 168 mL/min versus 305 ± 112 mL/min [P = .023] for *1/*1, 343 ± 127 mL/min versus 190 ± 93 mL/min [P = .008] for *1/*2, and 158 ± 54 mL/min versus 22 ± 11 mL/min for *2/*2) and is probably caused by inhibition of CYP3A4-mediated voriconazole metabolism. Conclusions Coadministration of a potent CYP3A4 inhibitor leads to a higher and prolonged exposure with voriconazole that might increase the risk of the development of adverse drug reactions on a short-term basis, particularly in CYP2C19 PM patients. Clinical Pharmacology & Therapeutics (2006) 80, 126-135; doi: 10.1016/j.clpt.2006.04.004